COMBINED EFFECT OF KITCHEN WASTE AND TERMITE SOIL COMPOSTS ON THE GROWTH OF TERRACE GARDEN PLANT - J. Kalaivani, C. Uma, P. Sivagurunathan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The termite mound soil added in different wastes for fermentation is to quick up the process and the Termite soil (TS) containing organisms act as a microbial starter. If we allowing composting the wastes under the natural landfills naturally the soil organisms involved in composting process. There is no need to accelerating the composting process by adding starter or any inoculums. The main aim of the study is the initiative experiment to minimize the procedures and manage the solid wastes and to allow composting process naturally and their effects on growth of terrace garden plant. The experiment showed that, composts containing termite soil organisms induced the plant growth and developments. Also, the application of Termite soil accelerated compost promoting the plant growth parameters.